ESTUDO DE PARÂMETROS PARA PRODUÇÃO DE BEBIDA FERMENTADA A PARTIR DO MEL - Chagas, Neucinéia Vieira (2008)
The Honey is a viscous food, sweet, pleasant aroma and according to some reports, it is appreciated since the ancient Greece. Parana State has a diverse apiculture flora and propitious conditions for the bee creation. Currently, Parana is the third in the national ranking on honey production, and in general, it produces a high-quality honey. The main objective of this work is to prepare a wine made from honey (Mead), and to verify what are the parameters that interfere at the speed fermentation. With that, it intents to add the honey value at the region, resulting in a drink, with good acceptance. The Mead is a fermented beverage which the basis is honey and water, consumed since the ancient times. Its manufacture is prior to the wine and beer. This fermented beverage is obtained by sugar and honey processing into alcohol. Aiming to prepare the mead in a reduced time and acceptable by the consumer market, a study was conducted from the honey fermentation with Saccharomyces cerevisiae. The fermentations were carried out with solutions of 16, 20, 21 and 28 Brix Degrees. These solutions were constrained in various conditions of temperature, time and means of fermentation. The final analysis was accompanied by the Brix Degree and then it was confirmed by tests in high performance liquid chromatography. The solutions were subjected to distillation and the alcohol content was determined by alcoholmeter, with the best results on the substrate conversion in ethanol to diluted honey solutions of 16° Brix and 28° Brix. The mass conversion of glucose into ethanol for these solutions was equal to 82.74% and 45.95% respectively. It was verified in this study that the fermentation of microorganisms without refueling in solutions with higher sugar content provides a lower yield of conversion of substrate in ethanol. A kinetic study was conducted to compare the speed of fermentation of diluted honey solutions with different compositions and another using glucose as the only source of carbon. The results allowed the determination of the mean to be used, it was found that the time for the exponential phase of fermentation is fourteen hours, and the complete consumption of glucose was determined after forty hours, through chromatographic analysis it was verified that there was preferential consumption by glucose.